MH-SETUP, combining Kesling wax-setup with indirect bonding and custom-made brackets for labial/lingual techniques to eliminate the finishing phase - Mohamed A Elkolaly; Hasan Sabah Hasan (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVE: A novel technique, named the MH setup (MH is an abbreviation for the author's name), was developed to provide an accurate yet simplified method to produce custom-made brackets without bonding errors. This setup aimed to simplify the treatment and eliminate the finishing phase, so that the orthodontist was able to provide better care with less time and lower costs. MATERIALS AND METHODS: The setup was performed in two major steps: direct bonding on the cast followed by cutting and setting the teeth into precise positions using brackets. The first set of brackets, bonded directly onto casts, oriented the teeth by setting them ideally into wax rims with full control over first-, second-, and third-order bends. The fully engaged archwire used allowed for precise control over the arch symmetry and form. Setting teeth in wax allowed the clinician to refine the occlusion and correct any minor errors that arose during the initial bonding. The second set of brackets, mounted on the fully engaged archwire, featured custom-made composite bases. The transfer tray combined the benefits of its soft inner and hard outer layers, providing control over bonding and later ease of peeling from the brackets. RESULTS: The patient was satisfied with a full bonding procedure lasting 15 min that remained simple without unnecessary stress. The clinician was confident that the procedure allowed the precise positioning of brackets and simple bonding for all teeth in the arch, combined with the elimination of the finishing phase. CONCLUSION: The MH technique offered a simple, precise, and inexpensive improvement to the Kesling wax setup. The process allowed for precise bonding without errors or expensive armamentarium. The brackets were transformed into custom-made prescriptions and could be used with labial or lingual techniques. The method allowed for teeth addition, trimming, or overcorrection according to the clinician's preferences. The MH setup facilitated visualization of the treatment objectives with precise locations and the opportunity to revise the treatment plan or to discuss further options with the patient.